1986
DOI: 10.1126/science.3006246
|View full text |Cite
|
Sign up to set email alerts
|

Antiserum to a Synthetic Peptide Recognizes the HTLV-III Envelope Glycoprotein

Abstract: In a study performed to determine which regions of the human T-cell lymphotrophic virus type III (HTLV-III) may represent vaccine candidates to prevent the acquired immune deficiency syndrome (AIDS), a synthetic peptide corresponding to amino acid sequence 735 to 752 of the precursor envelope glycoprotein of HTLV-III was used to immunize rabbits. The resulting rabbit antiserum to the synthetic peptide specifically recognized the precursor envelope glycoprotein (gp160) of HTLV-III. Human sera positive for antib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
80
0

Year Published

1986
1986
2011
2011

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(82 citation statements)
references
References 32 publications
2
80
0
Order By: Relevance
“…It is generally believed that the entire gp41 CT is located inside the cell. However, existing experimental and computational evidence suggest that the Kennedy sequence might lie outside the cell, because the antibodies against the Kennedy sequence can bind to virus-infected cells and neutralize HIV-1 infectivity (23,24). Our study focuses on the gp41 CT LLP1-2 region, especially the LLP1 and LLP2 regions that have been directly proven to be associated with the membrane fusion process (10,15), and aims to determine whether LLP1-2 directly or indirectly participates in the fusion reaction and, if so, to understand the underlying mechanism(s) of this event.…”
mentioning
confidence: 99%
“…It is generally believed that the entire gp41 CT is located inside the cell. However, existing experimental and computational evidence suggest that the Kennedy sequence might lie outside the cell, because the antibodies against the Kennedy sequence can bind to virus-infected cells and neutralize HIV-1 infectivity (23,24). Our study focuses on the gp41 CT LLP1-2 region, especially the LLP1 and LLP2 regions that have been directly proven to be associated with the membrane fusion process (10,15), and aims to determine whether LLP1-2 directly or indirectly participates in the fusion reaction and, if so, to understand the underlying mechanism(s) of this event.…”
mentioning
confidence: 99%
“…The antigenicity of this segment of the CT is very complex, and changes according to the biological context of gp41 (Reading et al, 2003). The Kennedy sequence, 731 PRGPDRPEGIEEEGGERDRDRS 752 , is exposed on the outer surface (Kennedy et al, 1986). It was observed that 3 epitopes 734 PDRPEG 739 , 740 IEEE 743 , 746 ERDRD 750 are mostly recognized in the Kennedy sequences (Chen et al, 2001;McLain et al, 2001).…”
Section: The C-term Tailmentioning
confidence: 96%
“…Then, since antibodies do not traverse the membrane and infectious virus are by definition intact, this suggests that part of the tail is exposed on the virion surface allowing antibody binding and neutralization, thus contrasting with the traditional intracytoplasmic location of the entire C-Term sequence of gp41 (Hollier & Dimmock, 2005). Studies have attempted to address this divergence between the old model of an exclusively intracytoplasmic tail and an alternative model with external segments of the CT, as the Kennedy peptide (aa731-752) (Kennedy et al, 1986) containing three patterns a conserved one 741 EEEGGE 746 and two others 747 QDRDRS 752 or 731 PRGPDRPGRI 740 . At the early steps of the viral entry, CT is implicated in the regulating of the kinetics of fusion and in the ability of Env to promote syncytia (Edwards et al, 2002;Wyss et al, 2005).…”
Section: The C-term Tail / Intra Cytoplasmic Tail (Ct/ics)mentioning
confidence: 99%
“…They also reacted with well conserved epitopes on gp41 because they recognized the HIV-1 RF strain, an isolate divergent from the immunizing HTLV-IIIB strain (Starcich et al, 1986;Myers et al, 1989) and did not react with HIV-2. Such conserved regions of gp41 had been already identified using synthetic peptides corresponding to residues 598 to 609 (Gnann et al, 1987a) and 735 to 752 (Kennedy et al, 1986b). Much evidence suggests that these regions are exposed at the surface of the virus (Chanh et al, 1986;Gnann et al, 1987b) and rabbit antisera and murine MAbs generated to the latter peptide neutralized HIV-1 and not HIV-2 infectivity in vitro (Chanh et al, 1986;Dalgleish et al, 1988).…”
Section: Discussionmentioning
confidence: 99%